High Seroprevalence of SARS-CoV-2 in White-Tailed Deer (Odocoileus virginianus) at One of Three Captive Cervid Facilities in Texas - Christopher M. Roundy; Chase M. Nunez; Logan F. Thomas; Lisa D. Auckland; Wendy Tang; Jack J. Richison; Breanna R. Green; Clayton D. Hilton; Michael J. Cherry; Alex Pauvolid-Corrêa; Gabriel L. Hamer; Walter E. Cook; et al. (Microbiology Spectrum, 2022)
ABSTRACT Free-ranging white-tailed deer (Odocoileus virginianus) across the United States are increasingly recognized for infection and transmission of SARS-CoV-2. Through a cross-sectional study of 80 deer at three captive cervid facilities in central and southern Texas, we provide evidence of 34 of 36 (94.4%) white-tailed deer at a single captive cervid facility seropositive for SARS-CoV-2 by neutralization assay (PRNT90), with endpoint titers as high as 1,280. In contrast, all tested white-tailed deer and axis deer (Axis axis) at two other captive cervid facilities were seronegative, and SARS-CoV-2 RNA was not detected in respiratory swabs from deer at any of the three facilities. These data support transmission among captive deer that cannot be explained by human contact for each infected animal, as only a subset of the seropositive does had direct human contact. The facility seroprevalence was more than double of that reported from wild deer, suggesting that the confined environment may facilitate transmission. Further exploration of captive cervids and other managed animals for their role in the epizootiology of SARS-CoV-2 is critical for understanding impacts on animal health and the potential for spillback transmission to humans or other animal taxa. IMPORTANCE As SARS-CoV-2 vaccine coverage of the human population increases and variants of concern continue to emerge, identification of the epidemiologic importance of animal virus reservoirs is critical. We found that nearly all (94.4%) of the captive white-tailed deer at a cervid facility in central Texas had neutralizing antibodies for SARS-CoV-2. This seroprevalence is over double than that which has been reported from free-ranging deer from other regions of the United States. Horizontal transmission among deer may be facilitated in confinement. Tracking new infections among wild and confined deer is critical for understanding the importance of animal reservoirs for both veterinary and human health.